2022
DOI: 10.3390/ijms232012293
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Seq Evaluation of Translation Driven by a Set of Natural Escherichia coli 5′-UTR of Variable Length

Abstract: Flow-seq is a method that combines fluorescently activated cell sorting and next-generation sequencing to deduce a large amount of data about translation efficiency from a single experiment. Here, we constructed a library of fluorescent protein-based reporters preceded by a set of 648 natural 5′-untranslated regions (5′-UTRs) of Escherichia coli genes. Usually, Flow-seq libraries are constructed using uniform-length sequence elements, in contrast to natural situations, where functional elements are of heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(49 reference statements)
0
3
0
2
Order By: Relevance
“…Similar observations relating to the low stability of the secondary structure and the conservation of the SD sequence were made for the variants determining a high translation efficiency [ 2 ]. The same factors were found to be significant for the translation efficiency of the reporter gene preceded by a set of natural 5’ UTRs; however, in this case, the variability of the translation efficiency was much lower than it was for the library of fully randomized 5’ UTR sequences [ 77 ]. There were also individual cases being indicative of the presence of AU-rich enhancers at the 5’ terminus at the standby site, low abundance of cytidine bases, multiple SD sequences, and AG repeats in the mRNA 5’ UTRs, which provide the high reporter protein level [ 2 ].…”
Section: The Scheme Of the Flow-seq Technique The Features And Result...mentioning
confidence: 99%
See 3 more Smart Citations
“…Similar observations relating to the low stability of the secondary structure and the conservation of the SD sequence were made for the variants determining a high translation efficiency [ 2 ]. The same factors were found to be significant for the translation efficiency of the reporter gene preceded by a set of natural 5’ UTRs; however, in this case, the variability of the translation efficiency was much lower than it was for the library of fully randomized 5’ UTR sequences [ 77 ]. There were also individual cases being indicative of the presence of AU-rich enhancers at the 5’ terminus at the standby site, low abundance of cytidine bases, multiple SD sequences, and AG repeats in the mRNA 5’ UTRs, which provide the high reporter protein level [ 2 ].…”
Section: The Scheme Of the Flow-seq Technique The Features And Result...mentioning
confidence: 99%
“…The Flow-seq method has been repeatedly used to gain insight into how the nucleotide sequences of different motifs of 5’ UTRs affect the translation efficiency. In particular, the ribosome binding sites with a fixed SD sequence [ 74 ], 5’ UTRs of different fixed lengths [ 2 ], or natural 5’ UTRs of different lengths [ 77 ], as well as standby sites and spacer regions [ 72 ], were studied. An analysis of tens of thousands of tested variants showed that the variation in the efficiency of the reporter protein synthesis can amount to four, and even five, orders of magnitude.…”
Section: The Scheme Of the Flow-seq Technique The Features And Result...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple high-throughput assays have been developed to validate the effect of 5'-UTR on protein translation rate, such as the Flow-seq and ribosome profiling (Ingolia et al 2009;Komarova et al 2022). Previous studies have concentrated on constructing 5'-UTR random libraries to screen out artificial 5'-UTR with high translation efficiency or exploring the influences of 5'-UTR sequence characteristics on protein translation efficiency by Flow-seq, such as secondary structure, the hybridization of the 16S rRNA to the RBS, AU enhancer (Osterman et al 2013).…”
Section: Introductionmentioning
confidence: 99%